Teknologi Dalam Pendidikan: Membantu Siswa Beradaptasi Dengan Revolusi Industri 4.0 - Asriani Alimuddin; Justin Niaga Siman Juntak; R. Ayu Erni Jusnita; Indri Murniawaty; Hilda Yunita Wono (Journal on Education, 2023)
The development of the industrial revolution demanded various changes in every activity, including in the field of education. Through technological developments in the learning process will be able to help students to face these challenges. This study aims to analyze the implementation of technology in education to help students face the challenges of the industrial revolution 4.0. This research is a descriptive qualitative research collecting data from literature study. The results of this study found that technology has a significant role in the world of education, especially in the era of the industrial revolution 4.0. Through the use of technology, students gain relevant skills and knowledge in the future. Then through the use of technology too, the creativity and innovation of students can be developed, as well as helping to establish social relations that are broader and also inclusive. Of course, in implementing this, careful planning is needed, so that the technology